1993
DOI: 10.1007/bf00181760
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoscintigraphy with technetium-99m labelled monoclonal antibody, 1A3, in colorectal cancer

Abstract: This study of radioimmunoscintigraphy (RIS) was primarily undertaken to determine how the imaging results related to surgical findings. Technetium-99m radiolabelled 1A3, a monoclonal antibody against a columnar cell surface antigen, was used. No adverse effects or thyroid uptake was observed in 127 studies. The 85 primary colorectal cancers were all image positive. In the assessment of recurrent tumour in the abdomen or pelvis, the accuracy was 33/35 (94%), including true-positive findings in some whose serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Historically, tumor-bound CEA has been used for cancer imaging and in vaccine and antibody-based therapeutic approaches for cancer treatment. [53][54][55][56] The antigen is limited to the apical surface and luminal portion of adult colonic epithelium under normal physiological conditions, but is overexpressed and loses its polarized distribution in CRC and other cancers resulting in expression of CEA over the entire cell surface. 57 This distribution in normal and neoplastic cells may result in specific targeting of CEA-positive tumor cells and sparing of normal colonic epithelium where T cell traffic is restricted to basolateral surfaces by the tight junctions separating apical and basolateral membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, tumor-bound CEA has been used for cancer imaging and in vaccine and antibody-based therapeutic approaches for cancer treatment. [53][54][55][56] The antigen is limited to the apical surface and luminal portion of adult colonic epithelium under normal physiological conditions, but is overexpressed and loses its polarized distribution in CRC and other cancers resulting in expression of CEA over the entire cell surface. 57 This distribution in normal and neoplastic cells may result in specific targeting of CEA-positive tumor cells and sparing of normal colonic epithelium where T cell traffic is restricted to basolateral surfaces by the tight junctions separating apical and basolateral membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work from our laboratory has shown that the antibody PR1A3, which is specific for membrane-bound carcinoembryonic antigen (CEA, formally designated CEACAM5), elicits ADCC against CEA-positive CRC cell lines even in the presence of super-physiological levels of free CEA (Durbin and Bodmer, 1987;Durbin et al, 1994;Conaghan et al, 2008). CEA is present on a high proportion of colorectal cancers, in which it is accessible to intravenously administered antibody, whereas in normal colorectal epithelium, due to the apical localisation of the antigen, it is not (Granowska, 1993). Radioconjugates targeting CEA have been used in early phase clinical trials in CRC (Wong et al, 2004;Liersch et al, 2005), but there is so far no unconjugated anti-CEA antibody licensed for treatment (Blumenthal et al, 2008).…”
mentioning
confidence: 99%
“…There have been many monoclonal antibodies developed to detect CRC antigens, with sensitivity ranging from 74% to 92%. These antigens include B72.3, carcinoembryonic antigen (CEA), BW431/21 and PR1A3 [37][38][39][40] . CEA molecules break off the colonic columnar cell membrane and circulate in the blood stream.…”
Section: Radioimmunoscintigraphymentioning
confidence: 99%